IMPORTANCE OF LOCAL CULTURE IN ADVERTISING: CASE OF SERBIA (Heritage, 2022)
The paper explores the importance of local culture in advertising in Southeast Europe, in particular in Serbia. The aim of the research was to examine whether there is any difference in perception among people in Serbia toward brands using local advertising campaign and brands using global advertising campaigns. The research included 520 respondents and the analysis included different statistical methods. The study examined the extent to which the influence of culture on the communication strategy is felt, and whether this impact is the same for all target audiences and for all product categories. The research reveals whether customers from Serbia prefer local or global campaigns, and whether the choice of the local versus the global has a more positive impact on brand perception. The findings showed some interesting and contradictory results: consumers prefer local advertisements rather than global campaign, though other finding indicate strong influence of globalization Serbia as represent of Southeast Europe countries.
Keywords: Culture, advertising, brand, communication, values, globalization